sSome biomechanicall variables related to the starting push and their relationship to the achievement of the 100m backstroke swimming for young people (Damu Journal of Sport Sciences, 2025)
This research aims to identify some of the biomechanical variables related to the starting push to perform the 100m backstroke swimming for youth, as well as to identify the relationship between the biomechanical variables related to the starting push and the performance of the 100m backstroke swimming for youth. To achieve the goal, the researcher used the descriptive approach using the correlation method to suit the problem and objectives of the research. The research sample was chosen intentionally. They are swimmers from the national team in the 100m backstroke, numbering (4) for the youth category, aged (15-17) years, which represents (80%) of the original research community, numbering (5) swimmers, as one of the swimmers was excluded due to injury. The researcher conducted the test as well as the video recording. After that, the researcher conducted the kinetic analysis of the swimmers using the analysis program (kinovea) to extract the biomechanical variables specific to the starting push. Appropriate statistical treatments were carried out. The researcher concluded that in the (push) stage, high correlations appeared with the achievement in both the variable of force and time of the push at the beginning of the race. This indicates its importance and the extent of its impact on the final result. The increase in the force of the push comes from the decrease in the time of the push due to the inverse relationship between them, which is generated through the speed of extending the body’s joints when pushing). Also, the angle of the push at the beginning of the race takes on a special character, as it must be larger than Zero, but on the condition that it approaches zero in the horizontal direction more than it approaches 90 degrees in the vertical direction. This is to achieve the greatest propulsion value and the least resistance against the water, in addition to maintaining horizontal flow in the water after exiting the propulsion phase.